El modelo de rotación por estaciones como estrategia metodológica activa para el aprendizaje de Biología Humana: Anatomía y Fisiología Humana con los estudiantes de Sexto Semestre de la Carrera de Pedagogía de las Ciencias Experimentales Química y Biología - Ilbay Guamán, Viviana Carolina (2024)
Active methodologies promote learning through strategies that motivate and inspire the student to recreate a technological paradigm, imbue learners with a real context, and use multifaceted resources that fascinate and capture the learner's attention. However, there are traditional methods that induce learning by repetition, increasing disinterest. The main objective of the research work was to propose the Model of Rotation by Stations as an active methodological strategy to contribute to learning Human Biology with the students of the Sixth Semester of the Pedagogy of Experimental Sciences, Chemistry, and Biology. The methodology of the study is part of the non-experimental design, a type of bibliographic and field research, with basic research focused on the quantitative and descriptive level, with the use of the inductive method. The survey was applied as a technique to obtain the data; it was applied to 13 students in the Sixth Semester. It was determined, in the results collected, that 100% agree that the active methodological guide based on the Rotation by Stations Model contributes to the development of scientific and technological competencies. It was concluded that this active methodology promotes student participation and collaboration, exchanging new and previous knowledge by incorporating workstations that stimulate learning styles. Given the above, it is proposed to use the active methodological guide as a source of information, oriented with attractive activities that facilitate the learning process in Human Biology.